General and silvicultura aspects of Cordia americana, Aspidosperma polyneuron, Toona ciliata e Khaya spp. (Revista de Ciências Agroveterinárias, 2016)
Brazil has a great diversity of forest species; however, the stands contain mostly species of Eucalyptus and Pinus. Faced with this, the present study is based on the analysis of the characteristics of native species with high potential and innovative character of timber species for cultivation. The Australian cedar (Toona ciliata) and African mahogany (Khaya spp.) are important species, mainly benefiting in reducing the exploitation of native forests remaining in the country. However, the species of (Cordia Americana) and (Aspidosperma polyneuron) show great potential yet to be explored, both in releasing commercial plantations and their proper use, that meets sustainability requirements.
Keywords: Forestry; cultivation; native species.